DAMPAK MEDIA SOSIAL TERHADAP PAHAM RADIKALISME - Andang Sunarto, PhD (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The purpose of this paper is to see the impact of social media on the idea of radicalism. In writing this paper using literature study method. And from the description in this paper can be concluded that social media have a positive and  negative impact. The negative impact of the free use of social media is the ease of accepting the Indonesian public receiving information including radicalism from all fields without finding out the truth of this information.